Colorectal Cancer‐Derived Small Extracellular Vesicles Promote Tumor Immune Evasion by Upregulating PD‐L1 Expression in Tumor‐Associated Macrophages (Adv. Sci. 9/2022). Issue 9 (25th March 2022) - Yin, Yuan; Liu, Bingxin; Cao, Yulin; Yao, Surui; Liu, Yuhang; Jin, Guoying; Qin, Yan; Chen, Ying; Cui, Kaisa; Zhou, Leyuan; Bian, Zehua; Fei, Bojian; et al.
Abstract : Small Extracellular Vesicles In colorectal cancer (CRC) tissues, tumor cell‐derived small extracellular vesicles (sEVs) miR‐21‐5p and miR‐200a synergistically induce macrophage M2 like polarization and PD‐L1 expression by regulating the PTEN/AKT and SCOS1/STAT1 pathways, resulting in decreased CD8 + T cell activity and increased tumor growth. More details can be found in article number 202102620 by Shenglin Huang, Zhaohui Huang, and co‐workers.